2019
DOI: 10.1002/chem.201901319
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of Macrocyclic Boronic Esters Bearing Tellurophene Moieties and Their Guest‐Responsive Phosphorescence

Abstract: Guest‐controlled diastereoselective self‐assembly of a diboryltellurophene and a chiral tetrol bearing an indacene backbone was achieved to give either hetero‐ or homochiral macrocyclic boronic esters, selectively. The heterochiral isomer (hetero‐[2+2]Te) exhibited a higher inclusion ability for electron‐deficient aromatic guests, leading to effective quenching of phosphorescence from the diboryltellurophene moieties. The reported macrocycles collectively represent a promising arene sensing approach based on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…In this context, an emerging solid-state ordering strategy relies on the use of boronic acids and derivatives to confine guests into a crystal lattice (Nishiyabu et al, 2011; Bull et al, 2013). The inclusion properties are facilitated by multiple supramolecular interactions of boronic acids and derivatives (e.g., hydrogen bonding (Campillo-Alvarado et al, 2018a,b; Ruelas-Alvarez et al, 2019), reversible esterification Fornasari et al, 2019; Takahashi et al, 2019, π-π interactions and B←N coordination Campillo-Alvarado et al, 2019; Ono and Hisaeda, 2019; Stephens et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, an emerging solid-state ordering strategy relies on the use of boronic acids and derivatives to confine guests into a crystal lattice (Nishiyabu et al, 2011; Bull et al, 2013). The inclusion properties are facilitated by multiple supramolecular interactions of boronic acids and derivatives (e.g., hydrogen bonding (Campillo-Alvarado et al, 2018a,b; Ruelas-Alvarez et al, 2019), reversible esterification Fornasari et al, 2019; Takahashi et al, 2019, π-π interactions and B←N coordination Campillo-Alvarado et al, 2019; Ono and Hisaeda, 2019; Stephens et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The requisite zirconacycle precursor 1 was first formed via a cyclization of bis­( para -biphenyl) acetylene bpCCbp and Cp 2 ZrPh 2 , as shown in Scheme (see Figure S2 for the X-ray structure of 1 ) . Following the Fagan–Nugent , protocol previously used in the Rivard group for the generation of tellurium- and bismuth-containing , heterocycles, compound 1 was reacted with 1 equiv of PCl 3 to generate the chlorophosphole 2 in a quantitative yield (Scheme ). As the Cp 2 ZrCl 2 byproduct from metallacycle transfer could not easily be separated from 2 , the product mixture of 2 /Cp 2 ZrCl 2 was used as is for further derivatization chemistry (vide infra).…”
Section: Resultsmentioning
confidence: 99%
“…In collaboration with the Rivard's and He's groups, we examined the self-assembly of the tellurophenediboronic acid and the photophysical properties of the obtained macrocyclic boronic esters. [32] In 2014, Rivard and his coworkers reported that 2,5-diboryl-substituted tellurophene (17) could undergo effective aggregation-induced phosphorescence, [33,34] both in the solid-state and in the presence of oxygen. We envisioned that the marriage of their and our concepts would realize a rare example of supramolecular tellurophene chemistry, possibly leading to guest-modulated changes in phosphorescence (Figure 12).…”
Section: Guest-responsive Phosphorescencementioning
confidence: 99%